Patient video compression using 3-D block transforms for telemedicine applications - Sriraam, N; Shyamsunder, , R; Eswaran, , C (2006)
This paper describes compression of patient videos using 3-D block transforms, namely discrete cosine, Hartley and Fourier. The transforms are applied on video image blocks of sizes 8x8xM where M represents the number of temporal frames considered in the transform. The resultant transform coefficients are quantized and then encoded using a combination of run length and Huffman coding schemes to achieve maximum compression. The performances of the three transforms are evaluated in terms of peak signal to noise ratio and bit rate. It is found from the experimental results, that the 3-D discrete cosine transform gives the best result.